Transient positive antimitochondrial M2 in sera of patients with connective tissue diseases after intravenous immunoglobulin infusions. Issue 4 (3rd November 2022) - Yang, Lijuan; Wei, Xiuning; Li, Qianhua; Li, Honggui; Ouyang, Zhiming; Zeng, Aiqi; Zheng, Donghui; Dai, Lie; Mo, Yingqian
Abstract: Background: Although antinuclear antibodies (ANAs), anti‐SSA and anti‐Ro52, are present in immunoglobulin preparations, it is unknown whether intravenous immunoglobulin (IVIG) therapy influences the testing of serum autoantibodies in patients with connective tissue diseases (CTDs). The present study aimed to investigate the dynamic change over time of serum ANA‐related autoantibodies in patients with CTDs receiving IVIG therapy. Methods: Serum ANA‐related autoantibodies were monitored in two patients with CTD before IVIG therapy and at different times after therapy. These autoantibodies were tested in different batches of immunoglobulin preparations from seven pharmaceutical companies. Results: One patient developed a new ANA pattern (cytoplasmic dense fine speckled pattern, AC‐19) just after IVIG therapy. Both patients developed de novo positivity for AMA‐M2 and anti‐SSA, but returned negative 1 month after IVIG therapy. The residual liquid in patients' immunoglobulin preparations showed positive ANAs with a high titer of AC‐19 (1:640), a low titer of the nuclear fine speckled pattern (AC‐4, 1:80), positive AMA‐M2, and positive anti‐SSA. ANA‐related autoantibodies were tested in 16 batches of immunoglobulin preparations and all had positive ANAs with two patterns: AC‐19 (1:640 or 1:320) and AC‐4 (1:80). AMA‐M2 and anti‐SSA were positive in 100% of the batches. Conclusion: Our study highlights high‐titer AMA‐M2 autoantibodies in immunoglobulin preparations and suggests their transient transfer into a patient's circulation via IVIG therapy. To avoid incorrect clinical decisions based on postinfusion antibody titers, our data recommend retesting 1–2 months after high‐dose IVIG immunomodulatory treatment. Abstract : High‐titer antimitochondrial M2 and anti‐SSA autoantibodies were present in immunoglobulin preparations. These autoantibodies were transferred transiently into the circulation of patients with connective tissue diseases via intravenous immunoglobulin (IVIG) therapy. Key points: High‐titer antimitochondrial M2 (AMA‐M2) autoantibodies were present in immunoglobulin preparations. The AMA‐M2 autoantibodies were transferred transiently into the circulation of patients with connective tissue diseases via intravenous immunoglobulin (IVIG) therapy. To avoid false clinical decisions based on postinfusion antibody titers, retesting 1–2 months after high‐dose IVIG immunomodulatory treatment was recommended.